Instagram Fake Profile Detection Using Machine Learning - Devendra Gharte; Akshay Rajguru; Prof. Khamkar P.J (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
With the rapid expansion of social media platforms, there has been a noticeable rise in the creation of fake profiles, often exploited for harmful purposes such as fraud, spreading false information, and online harassment. This study introduces a method for detecting fraudulent Instagram accounts through the application of Machine Learning, focusing on the Support Vector Machine (SVM) algorithm. The model distinguishes between authentic and fake profiles by analyzing features like the follower-to-following ratio, user engagement statistics, and the level of profile completion. The experimental findings indicate that the SVM model performs with high accuracy, proving to be an effective tool for enhancing digital safety.
Keywords: Fake Profile Detection; Instagram, Machine Learning; Support Vector Machine; Social Media Security